Combination of M-learning with Problem Based Learning: Teaching Activities for Mathematics Teachers - Zakaria, Mohamad Ikram; Abdul Hanid, Mohd Fadzil; Hassan, Roslizam (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This study was conducted to identify elements (teaching activities) that teachers can engage with involving a combination of M-learning methods with Problem-Based Learning methods (M-PBL). This study was conducted using the Nominal Group Technique (NGT) involving 11 experts with various fields of expertise such as mathematics education, educational technology, M-learning, pedagogy and the curriculum as well as primary school mathematics education teachers. The analysis of the findings was carried out using descriptive statistics (percentages) to determine the priority and ranking for each teaching activity. The findings show that overall, there are 30 relevant M-PBL teaching activities that can be carried out by teachers. The findings also show that teachers sharing the learning objectives that the pupils need to achieve using learning applications that are available on mobile devices (98%) ranked first while the teacher classifying the information obtained from each group according to priority through learning applications available on mobile devices (75%) ranked last. In conclusion, this study shows that both methods can be combined to form a new teaching method in the current 4.0 education era.